Cellule staminali mesenchimali associate a core-decompression nel trattamento delle necrosi cefaliche - Capuano, N.; Carbone, F.; Grillo, G.; D'Addona, A. (Lo Scalpello - Journal, 2019)
MESENCHYMAL STEM CELLS ASSOCIATED TO CORE DECOMPRESSION IN THE TREATMENTOF OSTEONECROSIS OF THE FEMORAL HEADOsteonecrosis of the femoral head often affects young active adults and leads to destruction of the hip joint and severearthritis. Various head-preserving procedures have been used to avert or delay the need for total hip arthroplasty. Nonvascularised bone grafting with core decompression is our preferred technique to treat surgically patients withpre-collapse ONFH. In this study we present a clinical case treated with Osteoplant flex scaffold (equinus bone graft)with mesenchymal stem cells.